2017
DOI: 10.1021/acs.organomet.7b00623
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II) Complexes with a Chemical and Redox-Active S2N2 Ligand: Structures, Electrochemistry, and Metal–Ligand Cooperativity

Abstract: Here we describe the synthesis, structures, and reactivity of Ru complexes containing a triaryl, redox-active S2N2 ligand derived from o-phenylenediamine and thioanisole subunits. The coordination chemistry of N,N′-bis­[2-(methylthio)­phenyl]-1,2-diaminobenzene [H2(MeSNNSMe)] was established by treating RuCl2(PPh3)3 with H2(MeSNNSMe) to yield {Ru­[H2(MeSNNSMe)]­Cl­(PPh3)}Cl (1). Coordinated H2(MeSNNSMe) was sequentially deprotonated to form Ru­[H­(MeSNNSMe)]­Cl­(PPh3) (2) followed by the five-coordinate, squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 55 publications
(92 reference statements)
4
26
0
Order By: Relevance
“…The terminal B− H resonances yielded a very broad resonance with a full width at half-maximum (fwhm) of 470 Hz centered at δ 1.22 ppm. The 11 B NMR spectrum in CD 2 Cl 2 also revealed a broad resonance at δ −18.3 ppm with no clear 11 B− 1 H coupling, but the solid-state IR spectra of 2-(BH 3 ) showed distinct bridging and terminal B−H stretches at 2346, 2417, and 2432 cm −1 , respectively. These are similar to B−H stretches reported for 1-(BH 3 ) at 2338 cm −1 (B−H−Ru) and 2404 and 2430 cm −1 (terminal B−H).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The terminal B− H resonances yielded a very broad resonance with a full width at half-maximum (fwhm) of 470 Hz centered at δ 1.22 ppm. The 11 B NMR spectrum in CD 2 Cl 2 also revealed a broad resonance at δ −18.3 ppm with no clear 11 B− 1 H coupling, but the solid-state IR spectra of 2-(BH 3 ) showed distinct bridging and terminal B−H stretches at 2346, 2417, and 2432 cm −1 , respectively. These are similar to B−H stretches reported for 1-(BH 3 ) at 2338 cm −1 (B−H−Ru) and 2404 and 2430 cm −1 (terminal B−H).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…These are similar to B−H stretches reported for 1-(BH 3 ) at 2338 cm −1 (B−H−Ru) and 2404 and 2430 cm −1 (terminal B−H). 11 Dual-MLC compound 1-(BH 3 ) 2 was prepared by refluxing RuCl 3 •xH 2 O with L1 and EtOH in air to form 1-Cl 2 , followed by reduction of 1-Cl 2 with 2 equiv of NaBH 4 (Figure 2a). Structures of 1-Cl 2 and 1-(BH 3 ) 2 obtained from single-crystal XRD studies revealed C s and C 2 symmetry, respectively, with chlorides and hydrides bound in the axial coordination sites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, complex 2 undergoes reversible oxidation to afford the corresponding cationic borohydride (Figure ). A cyclic voltammogram of 2 recorded in THF- n Bu 4 NPF 6 solution exhibits a redox event at −0.423 V ( i pa / i pc = 0.99), which is assigned to be a one-electron process for [ 2 ] +/0 . Oxidation of 2 by FcBAr F 4 on a preparative scale gave the cationic complex ( 2 + ) in 97% yield.…”
Section: Resultsmentioning
confidence: 99%